2013
DOI: 10.1103/physreva.88.013827
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effect of fractional degeneracy and the emergence of ray-wave duality in solid-state lasers with off-axis pumping

Abstract: We employ the inhomogeneous Helmholtz equation to explore the influence of the fractional degeneracy and the pump distdbution on the resonant lasing mode. Theoretical analyses clearly reveal the relationship between the fractional degeneracy and the emergence of the ray-wave duality. Furthermore, we perform thorough laser experiments to confirm the theoretical exploration that the resonant modes near the degenerate cavities are well localized on the ray trajectories under the condition of the off-axis pumping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 39 publications
1
48
0
3
Order By: Relevance
“…Detailed investigation by [8] revealed that the transverse modes in degenerate cavity are phase-locked with each other, leading to field addition of the modes rather than intensity addition (the latter observed in multitransverse mode lasers). The field addition may be responsible for the observed spot size, that is smaller than the TEM 00 spot expected for the cavity, and the arbitrary mode patterns [9,10] and pulse behavior [11,12] observed in such cavities. In a separate experiment, it was observed that this sudden collapse of the cavity mode is also accompanied by a corresponding increase in the M 2 parameter, and a dip in the output power [13].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Detailed investigation by [8] revealed that the transverse modes in degenerate cavity are phase-locked with each other, leading to field addition of the modes rather than intensity addition (the latter observed in multitransverse mode lasers). The field addition may be responsible for the observed spot size, that is smaller than the TEM 00 spot expected for the cavity, and the arbitrary mode patterns [9,10] and pulse behavior [11,12] observed in such cavities. In a separate experiment, it was observed that this sudden collapse of the cavity mode is also accompanied by a corresponding increase in the M 2 parameter, and a dip in the output power [13].…”
Section: Introductionmentioning
confidence: 92%
“…It is well-established that the lowest possible spot size, in a real stable resonator, is governed by the value of the TEM 00 spot allowed for the cavity, and the value of TEM 00 spot does not depend on the size of the pump spot [5]. However, when the resonator is driven exactly to the point of g1g2 1∕2, keeping the pump spot size less than the TEM 00 mode spot size at the gain medium, the cavity suddenly transforms to a cavity with new features, due to the onset of TMD [6][7][8][9][10][11][12][13]. The most exciting feature of the cavity is that the mode size can be even lower than the value decided by the TEM 00 mode size, and it is primarily governed by the size of the pump spot.…”
Section: Introductionmentioning
confidence: 99%
“…The optical resonator satisfying a degenerate state is called frequency-degenerate cavity (FDC). Without loss of generality, we consider a plano-concave laser cavity with the length of L, comprised of a gain medium, a concave spherical mirror with the radius of curvature of R, and a planar output coupler [30,31].…”
Section: A Frequency-degenerate Resonatormentioning
confidence: 99%
“…where z c is the location of the gain medium. Considering a selective pumping with the transverse displacements x and y in the x and y directions, the pump distribution F (x,y) can be modeled as [34] F (x,y) = 2 π…”
Section: Manifesting 3d Geometric Topology Of Laser Modesmentioning
confidence: 99%
“…In particular, the emergence of the ray geometry from the coherent wave in optical resonators is still an open and fascinating issue of active research in recent years. The attractive interest comes partly from the fundamental questions of light-matter interaction [31] and ray-wave correspondence [32][33][34], and partly from numerous applications, such as cavity spectroscopy [35][36][37], optical pattern formation [38][39][40][41], single-photon emitters [42], and ultralow threshold lasers [43,44].…”
Section: Introductionmentioning
confidence: 99%